2015
DOI: 10.1590/1519-6984.21513
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive features of the swimming crab Callinectes danae(Crustacea, Portunoidea) on the subtropical coast of Brazil: a sampling outside the estuary

Abstract: The life cycle of the crab Callinectes danae is estuarine-dependent, and studies on aspects of their biology should also cover marine areas. The present study investigated the sexual maturity, as well as habitat preference by adults in different gonadal stages, and the crabs' reproductive periodicity outside the estuary. Three bays on the subtropical southeastern coast of Brazil were sampled monthly for two years. For each bay, six transects were established, four of them parallel to the beach line (5, 10, 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The early sexual maturity of females is a constant in both species, since similar studies have also observed this pattern in both sexes (see Table 2 for review). This sexual dimorphism (particularly related to morphometric maturity) is part of the reproductive strategy of portunids, in which pre-and post-copulatory guards are typical and larger adult males take more advantage in protecting females, guaranteeing the paternity of the offspring (Hartnoll, 1969;Sastry, 1983;Pinheiro and Fransozo, 1998;Mantelatto and Fransozo, 1999;Baptista et al, 2003;Andrade et al, 2015). Thus, after the puberty molt, males direct greater amount of metabolic energy to somatic growth, while females invest their energy in reproductive processes, leading to early sexual maturity and longer fertile life, increasing the reproductive output of the population (Hartnoll, 1985;Avila and Branco, 1996;Baptista-Metri et al, 2005;Fernandes et al, 2006;Keunecke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early sexual maturity of females is a constant in both species, since similar studies have also observed this pattern in both sexes (see Table 2 for review). This sexual dimorphism (particularly related to morphometric maturity) is part of the reproductive strategy of portunids, in which pre-and post-copulatory guards are typical and larger adult males take more advantage in protecting females, guaranteeing the paternity of the offspring (Hartnoll, 1969;Sastry, 1983;Pinheiro and Fransozo, 1998;Mantelatto and Fransozo, 1999;Baptista et al, 2003;Andrade et al, 2015). Thus, after the puberty molt, males direct greater amount of metabolic energy to somatic growth, while females invest their energy in reproductive processes, leading to early sexual maturity and longer fertile life, increasing the reproductive output of the population (Hartnoll, 1985;Avila and Branco, 1996;Baptista-Metri et al, 2005;Fernandes et al, 2006;Keunecke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Keunecke et al (2012) also found percentages of immature C. danae (16.2%) and C. ornatus (85.6%) females captured by trawling pink shrimp. Populations of overfished portunids can have their asymptotic size reduced and, consequently, the size of maturity can also decrease, reducing the fertility and reproductive output of the population (Keunecke et al, 2012;Andrade et al, 2015). Based on this assumption, the mesh of traps used in the swimming crab fishing at São Francisco do Paraguaçu and other fishing areas of the Todos os Santos Bay should be adjusted to prevent immature animals from being captured.…”
Section: For Review)mentioning
confidence: 99%
“…Adults and ovigerous females of C. danae migrate to deeper areas with favorable salinity and current conditions that provide the needed embryonic and larval development and dispersion, similarly observed in C. ornatus (see Mantelatto, 2000). Furthermore, the characteristics of each ecosystem determine how the species migrates between different habitats within its range (Keunecke et al, 2009;Andrade et al, 2015).…”
Section: Influence Of Day/night Periods In the C Danaementioning
confidence: 99%
“…The knowledge of a species' reproductive biology is extremely important for the understanding of its life cycle. It also helps planning a more sustainable use of resources so that they can be a source of income for local communities without harming the populations (Andrade et al, 2015). In this way, aiming to support the economic and social development as well as the environmental protection of the region ("Triângulo Mineiro"), we investigated the reproductive cycle of M. amazonicum, focusing on the spatio-temporal abundance of breeding females.…”
Section: Introductionmentioning
confidence: 99%